Mortality rate of newly hatched larvae of Nile tilapia (Oreochromis niloticus) submitted to different photoperiods - Márcia Dantas dos Santos; Bernadete de Oliveira Costa; Jucilene Pereira de Sousa; Neila Lidiany Ribeiro; Marino Eugênio de Almeida Neto; Ian Porto Gurgel do Amaral (Universidade Estadual de Alagoas, 2021)
ABSTRACT: Fish farming is a growing area in the aquaculture industry. Brazil is among the five largest tilapia producers in the world, with a production of 283 thousand tons in 2017. Tilapia has been intensively cultivated and improved through more efficient cultivation techniques. In this sense, the objective was to evaluate the mortality rate of newly hatched larvae of Nile tilapia reared three photoperiods (12Light:12Dark, 18L:06D, and 24L:0D) during 9 days of cultivation. For this purpose, a recirculation system with 9 water tanks was set up, with 3 boxes per group containing 930L of freshwater. After the embryos hatched, the larvae were transferred to nurseries (2 trays per tank, n = 64 larvae/tray), with 384 larvae per photoperiod. Water quality parameters were monitored and remained in the ideal ranges between treatments. However, temperature (p=0.004) and pH values (p= 0.009) for the 18L:06D photoperiod were lower than those observed for the 24L:0D photoperiod. A high mortality rate was observed in the first days of culture, specifically on the second day, for all photoperiods. However, there was a decrease in mortality throughout the experiment, with little variation in the mortality rate for the remainder of the experiment. In this context, it appears that the influence of the photoperiod on the survival of the fish seems to be related to the age of the animal.   KEYWORDS: Tilapia farming, Survival, Light stimulation.